Iterative Algorithms for a Finite Family of Multivalued Quasi-Nonexpansive Mappings. (13th November 2014) - Diop, C.; Sene, M.; Djitté, N.
Abstract : LetK be a nonempty closed and convex subset of a uniformly convex real Banach spaceE and letT 1, …, T m : K → 2 K bem multivalued quasi-nonexpansive mappings. A new iterative algorithm is constructed and the corresponding sequencex n is proved to be an approximating fixed point sequence of eachT i ; that is, lim d x n ; T x n = 0 . Then, convergence theorems are proved under appropriate additional conditions. Our results extend and improve some important recent results (e.g., Abbas et al. (2011)).